Impact of statin use and lipid profile on symptomatic intracerebral haemorrhage, outcome and mortality after intravenous thrombolysis in acute stroke - Rocco, Andrea; Sykora, Marek; Ringleb, Peter A.; Diedler, Jennifer (Cerebrovascular diseases, 2012)
Background: It is unclear if a certain lipid profile and/or statin use contribute to symptomatic intracerebral haemorrhage (sICH), poor outcome or mortality after intravenous thrombolysis for ischaemic stroke. The aim of the current study was to assess the impact of statin use and lipid profile on sICH, outcome and mortality following thrombolysis in acute stroke. Methods: From 2001 to 2010, all patients admitted to our hospital and undergoing intravenous thrombolysis for acute ischaemic stroke were included into an open, prospective database. Initial stroke severity was assessed using the National Institute of Health Stroke Scale. Demographics, vascular risk factors, admission blood pressure, glucose levels, previous medication including statin use, lipid profiles including low-density lipoprotein (LDL), high-density lipoprotein (HDL) and triglyceride levels were recorded. Outcome measures included sICH according to the European Cooperative Acute Stroke Study II criteria, modified Rankin scale and mortality at 3 months. Results: 1,066 patients were included in the analysis; 5.3% (57 patients) had sICH. Mortality at 3 months was 17.6% (188 patients). A favourable outcome (modified Rankin scale 0-1) at 3 months was attained by 35.6% (379 patients). Prior statin use was not associated with increased odds for sICH (OR 1.05, 95% CI 0.55-2.04, p = 0.864), mortality (OR 1.32, 95% CI 0.90-1.93, p = 0.152) or favourable outcome (OR 0.89, 95% CI 0.65-1.24, p = 0.507). Similar results were found for the different lipid variables: high LDL (OR 0.96, 95% CI 0.36-2.60, p = 0.942), high triglyceride (OR 1.74, 95% CI 0.84-3.56, p = 0.132) and low HDL (OR 1.78, 95% CI 0.68-4.65, p = 0.279) were not associated with increased odds for sICH. Likewise, neither mortality nor functional outcome at 3 months was significantly associated with any of the lipid variables in the univariable analysis following Bonferroni adjustment for multiple comparisons. The same results were found in the multivariable analysis adjusting for imbalances in baseline characteristics. Conclusions: In contrast to previous studies, we found that in stroke patients receiving thrombolysis therapy, neither the lipid profile nor prior statin use were associated with increased odds for sICH, functional outcome or mortality at 3 months.